Complex Bedrock Fracture Patterns: A Multipronged Approach to Resolve Their Evolution in Space and Time. Issue 4 (6th April 2018) - Scheiber, Thomas; Viola, Giulio
Abstract: The complex fault and fracture patterns commonly observed in metamorphic terranes are the cumulative expression of repeated episodes of brittle deformation. The temporal sequence of deformation remains, however, often obscure due to the general lack of systematic overprinting relationships and absolute geochronological constraints. Here we present a multipronged approach combining remote sensing, field work, structural analysis, and paleostress inversion with mineralogical characterization and K‐Ar dating of brittle features to develop an evolutionary model for one such complex fracture pattern. We applied this methodological approach to pervasively fractured Early to Middle Ordovician intrusive rocks in the northern Bømlo islands, SW Norway. The local brittle structural record is interpreted as reflecting a sequence of six deformation stages, three ascribable to the Caledonian orogenic cycle and three to the rift evolution of the North Sea. The Caledonian structures are assigned to (1) Late Ordovician NNW‐SSE transpression, (2) Silurian ESE‐WNW compression, and (3) Devonian NW‐SE transtension. The rift‐related structures formed during (4) Permian to Middle Triassic ENE‐WSW extension ( 290–245 Ma), (5) Late Triassic to Late Jurassic E‐W extension ( 210–160 Ma), and (6) Early Cretaceous ESE‐WNW extension ( 125 Ma). The reconstructed gradual rotation of the extensional stress field during the Mesozoic might reflect the continuous northward migration of the rift activity from the North Sea toward the mid‐Norwegian margin. Our multipronged approach may be applied to the unraveling of complex and commonly long brittle histories stored in exhumed metamorphic terranes elsewhere. Key Points: Combined structural, mineralogical, and geochronological studies unravel the temporal and spatial evolution of bedrock fracture patterns The investigated fractures in SW Norway formed mainly during the Paleozoic Caledonian orogeny and episodic Permian and Mesozoic rifting By the Middle Triassic, all the structural elements defining the currently exposed fracture pattern were largely established